Clinical and Radiologic Outcomes of Volar Plate Fixation in AO Type C Distal Radius Fractures - Ahmet Şenel (İstanbul Medical Journal, 2018)

(untitled)
Introduction: To evaluate the clinical and radiological outcomes of anatomic volar plate application in AO type C distal radius fractures.Methods: Patients who were operated on between January 2015 and April 2016 due to AO type C distal radius fracture were screened retrospectively from the hospital file and radiology archive. Clinical outcomes were determined by the disabilities of the arm, shoulder, and hand (DASH) score from outpatient records. The Stewart radiological scores were assessed with the measurements obtained from radiology archives. The complications were noted.Results: Overall, 16 patients (mean age, 52 years) were included in the study. In total, 9 of the patients were female, and 7 of the patients were male. The mean follow-up period was 11.9 months. The mean DASH score was 33.9, and the mean Stewart radiological score was 0.9. The bone union was accomplished in all patients. One infection, one joint stiffness, one carpal tunnel syndrome, and 2 tendinitis were observed as complication.Conclusion: Volar plate fixation in the AO type C distal radius fractures provides satisfactory results in terms of either clinical or radiological outcomes. Despite that, the complications regarding surgery and the implants are not rare.